CLINICAL-NEUROPHYSIOLOGICAL FEATURES IN PATIENTS WITH REPEATED CEREBRAL ISCHEMIC HEMISPHERIC STROKE IN ACUTE PHASE OF DISEASE - Kozolkin, O. A.; Novikova, L. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Summary. In order to study the clinical and neurophysiological features in patients with recurrent cerebral ischemic hemispheric ischemic stroke (RCHIS), a comprehensive clinical-paraclinical study of 49 patients (28 men and 21 female, mean age 72 (63; 76) years) in the acute period of the disease was conducted. It was found domination of mild and moderate dementia, the median total NIHSS score in the debut of the disease consisted 10 (7; 13), which corresponded to the average severity of the stroke. It was found that the parameters of δ-rhythm APS, δ-rhythm RSP and β rhythm relative spectral power have the strongest correlation with level of neurological deficit by NIHSS score and with level of disability by MRS, as well as parameters of occipital-frontal grade of βhi-rythm and hemispheric asymmetry of αlo-subband correlated with the level of cognitive deficit.